Early Frameshift Mutation in PIGA Identified in a Large XLID Family Without Neonatal Lethality. Issue 3 (13th January 2014) - Belet, Stefanie; Fieremans, Nathalie; Yuan, Xuan; Van, Hilde; Verbeeck, Jelle; Ye, Zhaohui; Cheng, Linzhao; Brodsky, Brett R.; Hu, Hao; Kalscheuer, Vera M.; Brodsky, Robert A.; Froyen, Guy
<x xml:space="preserve">Abstract</x> Loss‐of‐function mutations in the PIGA gene are normally lethal in utero. In this study however, we report a loss‐of‐function PIGA mutation in boys from a large family who were diagnosed with a severe form of intellectual disability. Based on functional assays, we provide evidence that this mutation results in the production of a shorter PIGA protein with residual functionality which is sufficient to rescue the lethality but still results in clinical features including intellectual disability. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>